Pengaruh Luxury Branding Dior Addict Lip Tint Terhadap Self Identity Konsumen Generasi Z Di Jabodetabek - Jessica Adeline Clarissa; Rachel Viera Lambert; Deddy Muharman (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the effect of luxury branding of Dior Addict Lip Tint on the self-identity of Generation Z consumers in the Greater Jakarta area. The increasing consumption of luxury beauty products indicates that Generation Z does not purchase products solely for functional purposes, but also to express self-identity and social image. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 385 Generation Z respondents in Greater Jakarta who have used Dior Addict Lip Tint. Data analysis techniques include validity testing, reliability testing, and statistical analysis to examine the relationship between luxury branding as the independent variable and self-identity as the dependent variable. The results show that luxury branding has a significant influence on the formation of Generation Z consumers' self-identity. An exclusive, prestigious, and high-quality brand image enhances consumers’ perception of self-identity and strengthens their emotional attachment to the brand. These findings indicate that luxury branding strategies play a crucial role in building the symbolic value of products and in shaping how young consumers perceive and express their self-identity through beauty product consumption.